Investigation of Special Education Department Research Assistants' Perceptions of Teaching Practice Course - Yunus Yılmaz; Hamdi Gönüldaş; Göksel Cüre; Tüncay Tutuk; Ahmet Serhat Uçar (Anı Publishing, 2023)
This study aims to examine the perceptions of research assistants in the department of special education about the teaching practicum course in the VII. and VIII. semester. Eight research assistants who conducted teaching practicum courses in the field of special education participated in the phenomenological approach. The data obtained through semi-structured interviews were analyzed through inductive analysis. The findings include the perceptions of the practice kit, the roles of the research assistants in the teaching practicum process, the grading of the students, and the perceptions of the teaching practicum process from the perspective of the students from the practitioner's point of view. On the other hand, the study recommends shortening the lesson plans and making them clear, understandable and usable.